The Levi-Civita space-time - Da Silva, M. F A [UNESP]; Herrera, L.; Paiva, F. M.; Santos, N. O. (AIP Publishing, 1995)
Two exact solutions of Einstein's field equations corresponding to a cylinder of dust with net zero angular momentum are considered. In one of the cases, the dust distribution is homogeneous, whereas in the other, the angular velocity of dust particles is constant [Nuovo Cimento B 21, 64 (1974)]. For both solutions the junction conditions to the exterior static vacuum Levi-Civita space-time were studied. From this study we find an upper limit for the energy density per unit length σ of the source equals 1/4 for both cases. Thus the homogeneous cluster provides another example [Class. Quant. Grav. 8, 727 (1991); J. Math. Phys. 27, 152 (1980)] where the limit of σ is 1/4. It was also found that the cluster of homogeneous dust has a superior limit for its radius, depending on the constant volumetric energy density ρ 0. © 1995 American Institute of Physics.